Factors Influencing Pre-Hospital Delay In Patients with Acute Myocardial Infarction (University Heart Journal, 2019)
Acute coronary syndrome is a lethal condition. Treatment modality and success mostly depend on time yielded since onset of symptoms. It is known for more than 30 years that delay between symptom onset and treatment of less than 60 min are desirable, but pre hospital delays remain unacceptably long worldwide including Bangladesh. A greater understanding of the contributing factors may help to reduce delays. A number of sociodemographic, clinical, social and proximal factors have been associated with pre hospital delay. The total pre hospital delay period consists of two component: time taken by patients to recognize that their symptoms are serious and to contact medical help (decision time) and the time taken from requesting help to admission where emergency coronary care is available (time to hospital delay). Different factors may affect these two components. In hospital delay also known as door-to-treatment, is defined as time from arriving to hospital to initiation of reperfusion therapy. Regardless of how to shorten in hospital delay, if the pre hospital delay is not reduced, then reperfusion therapy cannot achieve the best results. We set out to discover what factors are specifically associated with three components: decision time, home to hospital delay and First Medical Contact (FMC) to revascularization delay. This review may help the National health management system to identify the factors associated with treatment delay in ACS and thus reduces ACS related morbidity and mortality.University Heart Journal Vol. 15, No. 2, Jul 2019; 79-85